Enhanced efficiency of organic light-emitting devices with corrugated nanostructures based on soft nano-imprinting lithography - Liu, Yue-Feng; An, Ming-Hui; Zhang, Xu-Lin; Bi, Yan-Gang; Yin, Da; Zhang, Yi-Fan; Feng, Jing; Sun, Hong-Bo (Applied physics letters, 2016)
An enhanced efficiency organic light-emitting device (OLED) with corrugated nanostructures on a small-molecule organic film has been demonstrated. By patterning the hole transport layer via soft nano-imprinting lithography and coating with Ag, a nanostructured cathode is introduced to enhance the light extraction of the OLED without affecting the flatness and conductivity of the indium-tin-oxide film. Both luminance and current efficiency are improved compared with those of conventional planar devices. The observable improvement in luminance and current efficiency can be ascribed to the surface plasmonic and scattering effects caused by the Ag nanostructures. Moreover, theoretical simulations also demonstrate that the power loss to surface plasmon-polariton modes has been recovered.